Sidewall influence of varying free stream Mach number in ramp induced shock wave boundary layer interactions - Raja Mangalagiri; Satya P Jammy (Theoretical and Applied Mechanics Letters)
This study investigates the three-dimensional (3D) effects introduced by the end walls for an aspect ratio of 1 in ramp-induced shock wave boundary layer interactions. The simulations are performed using a symmetry boundary condition in the spanwise direction at free-stream Mach numbers in 3D. The simulations are performed using an in-house compressible supersonic solver “OpenSBLIFVM”. Two free stream Mach numbers 2.5, and 3 are used in the current work, and the simulated results are compared with the aspect ratio 1 simulations by Mangalagiri and Jammy. The inflow is initialized with a similarity solution; its Reynolds number based on the boundary layer thickness is adjusted such that the Reynolds number at the start of the ramp is kept at 3×105 for all simulations. From the results, it is evident that the introduction of sidewalls resulted in a shorter centerline separation length when compared with the two-dimensional (2D) simulations. This contradicts the results at Mach 2 by Mangalgiri and Jammy where the vortex observed at Mach 2 in the central separation region disappeared with increasing free-stream Mach number. Additionally, the topology of interaction shifted from owl-like separation of the second kind to the first kind when the freestream Mach number increased from 2 to 2.5. It can be concluded that the interaction topology is crucial to the increase or decrease of the central separation length when compared to 2D simulations.